Продукція цитокінів клітинами кордової крові та імуномодулювальні властивості плазми кордової крові - Лазаренко, Л.М.; Рачкова, Л.Т.; Демченко, О.М.; Байдик, О.О.; Співак, М.Я. (Видавничий дім "Академперіодика" НАН України, 2008)
Cord blood cells in vitro spontaneously produce cytokines of the Th1type, interferon-γ and interleukin-2, as well as interferon-α and tumor necrosis factor-α which are implicated into the regulation of the production of cytokines of the Th1type. As a response to the adequate induction, the production of interferon, interleukin-2, and tumor necrosis factor-α was not increased, which testifies to a decrease of the cellular functional reserve of the cells producing these cytokines. Immune regulative cytokines are found in the plasma of cord blood that increases the functional activity of cells of the phagocytes system in vitro.